The Reflexive Aspect of the Perception of Each Other by the Subjects of the Conflict - Anikina, V.G.; Lagutin, A.V. (Psihologičeskaâ nauka i obrazovanie, 2022)
The reflexive aspect of the perception of the subjects of the conflict became the main issue of the presented work. In the framework of the experimental study, the level of reflexivity (A.V.Karpov), the styles of leading behavior (the Thomas-Kilmann Method), as well as the assessment of the personality image (the Petrovsky-Uvarina Scaling Method) were diagnosed.The experiment was carried out using the created installation "Experiment for the Study of Negotiations" (the idea by V.A.Lefebvre, modification by B.I.Khasan).It was shown that the opponent's image significantly changes for respondents with a " low" level of reflexivity. Respondents with a "high" level of reflection are more differentiated in their assessment of the opponent in the conflict interaction. The change in the opponent's image is carried out to a greater extent by the respondents who end the conflict interaction with a compromise. It was revealed that a change in the leading behavior in a conflict is more typical for respondents with "medium" and "high" levels of reflection. A statistically significant positive relationship was determined between the level of reflexivity and a change in the style of behavior in the conflict interaction. The results obtained in the future will make it possible to simulate the process of getting out of the conflict and use the potential of virtual reality to work with conflict situations. Представлены материалы исследования рефлексивного аспекта про¬блемы восприятия субъектов конфликта. В рамках экспериментального исследования диагностировались уровень рефлексивности (А.В.Карпов), стили ведущего поведения (методика Томаса—Килманна), а также оцен¬ка образа личности (метод шкалирования Петровского—Увариной). Экс¬перимент проводился с помощью созданной установки «Эксперимент для изучения переговоров» (идея В.А.Лефевра, модификация Б.И.Хасана).Было показано, что достоверно изменяется образ оппонента у респонден¬тов с «низким» уровнем рефлексивности. Установлено, что респонденты с «высоким» уровнем рефлексии более дифференцированно подходят к оцениванию оппонента в конфликтном взаимодействии. Изменение образа оппонента в большей степени осуществляют респонденты, которые завер¬шают конфликтное взаимодействие компромиссом. Выявлено, что измене¬ние ведущего поведения в конфликте более характерно для респондентов со «средним» и «высоким» уровнями рефлексии. Определена статистиче¬ски достоверная положительная связь между уровнем рефлексивности и сменой стиля поведения в конфликтном взаимодействии. Делается вывод о том, что полученные результаты в дальнейшем позволят осуществить моделирование процесса выхода из конфликта и использовать потенциал виртуальной реальности для работы с конфликтными ситуациями.